Biological properties of coronaviruses of farm, domestic animals and birds: comparative characterization of pathology they induce (review) - Kh. Z. Gaffarov; A. I. Yarullin; V. G. Gumerov; I. G. Karimullina (Ветеринария сегодня)
Coronavirus induced diseases can cause significant damage to agriculture that is associated with high (up to 100%) lethality in young animals. Members of the family Coronaviridae are characterized by the fact that they infect a wide range of animals and birds with expressed species-limited  pathogenicity.  One more coronavirus specificity involves their ability to simultaneously affect more than one organ. The disease severity is also strongly correlated with the age of the susceptible animal and degree of pathology. Thus, the coronavirus induced diseases are most often acute in newborn and young animals, while such diseases often develop into chronic and latent forms in adult animals. The general property of all coronavirus-induced diseases involves acute impairement of capillary circulation in the affected organ thus leading to the development of further pathology. The proposed review demonstrates  brief overview of the history of discovery and examination of the viruses of Coronaviridae family and describes the coronavirus taxonomy. The paper reviews the virus structure, physico-chemical and biological properties; it describes specific features  of their cultivation in vitro, some biochemical aspects of the virus replication and analyses the process of their propagation  in the sensitive cells. Some data on the virus antigen structure and immunogenicity, on the presence of related antigens in the coronaviruses infecting humans, animals and birds are demonstrated as well. The paper provides data on the significant role the coronaviruses play in the pathology of farm animals and stresses their economic relevance, in particular for the commercial pig and poultry production.